The Role of the organization of The Naval Academy in Accordance with The Criteria for Development of Public Administration - Moungyai, Anucha (Journal of Thammawat, 2022)
The Article is about "The role of the organization of the Naval Academy in accordance with the criteria for development of public administration." which is has an objective of studying the Royal Thai Naval Academy operation method especially in the first section. The result from the study can be used as a guideline for development of Royal Thai Naval Academy to meet the standard criteria, as well as, to develop the management system of Royal Thai Naval Academy to become the best and to raise the level of operational quality to be in line with the goals in accordance with the principles and methods of good government administration. The study focuses on bureaucratic administration for the benefit of the people. The result of the study found that the definition of the school’s vision should have a clear definition. Second, to determine the school’s values should be consistently defined to become a good corporate culture. Third, to create a good organization atmosphere, the Royal Thai Naval Academy leader must manage the activities, and encourage and motivate the personnel of The Royal Thai Naval Academy to get involved in. Finally, the leader should promote the role of social responsibility. Royal Thai Naval Academy should be conducted on the basis of the organization’s potential with clear directions in the strategic plan of the Royal Thai Naval Academy.